Effectiveness of multi-shape laser surface texturing in the reduction of friction under lubrication regime. Issue 1 (8th February 2016) - Segu, Dawit Zenebe; Hwang, Pyung
Abstract : Purpose: – The purpose of this paper is to investigate and discuss the effect of multi-shape laser surface texturing (LST) steel surfaces on tribological performance. Design/methodology/approach: – The textured surface with some specific formula arrays was fabricated by laser ablation process by combining patterns of circles and triangles, circles and squares and circles and ellipses. The tribological test was performed by a flat-on-flat tribometer under dry and lubrication conditions, and results were compared with that of untextured surface. Findings: – The results showed that the textured surface had better friction coefficient performance than the untextured surface due to hydrodynamic lubrication effect. Through an increase in sliding speed, the beneficial effect of LST performance was achieved under dry and lubrication conditions. Originality/value: – This paper develops multi-shape LST steel surfaces for improving the friction and wear performance under dry and lubrication conditions.